Afterword: So what is the anthropology of Buddhism about? - Gellner, DN (Berghahn Journals, 2017)
This afterword considers the history of the subfield of the anthropology of Buddhism in light of the essays in this special section of Religion and Society. Anthropologists have sought to combat conventional assumptions about Buddhism and have long made contributions to the study of Buddhism, the state, nationalism, and politics. As part of a maturing field, they have also made contributions through the study of Buddhism to many other subfields of anthropology, including morality, spirit possession, the emotions, and materiality. It is no longer necessary for the anthropology of Buddhism to be overwhelmingly concerned with the authenticity and identity of its subjects.